The Design of the Nusantara Quest Game on Mobile Platforms for the Cultural Arts Subject for Grade X Students - Fahril, Muhammad; Usman M; Muhammad Takdir (International Journal of Sustainable Applied Sciences, 2024)
This research aims to design a mobile-based game called Nusantara Quest to enhance student engagement and learning outcomes in Arts Education for 10th-grade students. The educational game is developed using the Unity platform and follows the ADDIE model (Analyze, Design, Development, Implementation, Evaluation). The analysis phase involves studying student characteristics and material needs. During the design phase, game flow, user interface, and educational content are created. The development phase includes game creation and validation by media and content experts. Implementation involves trials with students from SMK Negeri 5 Sidrap, and the evaluation phase assesses the effectiveness of the game in improving student interest and understanding of Arts Education material. The research findings indicate that the quiz-based educational game is valid and effective as an interactive learning media S